2014
DOI: 10.1166/jnn.2014.8255
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance of Functionalized IRMOF-3 for the Synthesis of Glycerol Carbonate from Glycerol and Urea

Abstract: A functionalized isoreticular metal organic framework material, F-IRMOF-3, having a quaternary ammonium group was prepared by fast precipitation and solvothermal method. The synthesized MOFs exhibited good catalytic performance in the synthesis of glycerol carbonate (GC) from glycerol and urea. F-IRMOF-3 having a larger alkyl chain structure and a more nucleophilic counter anion than the synthesized congeners, exhibited better reactivity in the synthesis of GC. The introduction of a ZnO defect into the F-IRMOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was found that the catalyst bifunctionality, that is, the simultaneous presence of the acid and basic sites, contributed significantly to the catalyst performance in the synthesis of cyclic carbonates from urea and diols. A bifunctional MOF catalyst having an appropriate combination of Lewis acid and Lewis basic sites was developed specifically for this process [97]. This material, that is, the IRMOF-3 framework (Zn 4 O(BDC) 3 ) with amino functions in organic linkers was modified by a post-synthesis strategy by alkyl halides resulted in the conversion of -NH 2 to a quaternary ammonium salt species.…”
Section: Post-synthesis Modification Of Organic Linkersmentioning
confidence: 99%
“…It was found that the catalyst bifunctionality, that is, the simultaneous presence of the acid and basic sites, contributed significantly to the catalyst performance in the synthesis of cyclic carbonates from urea and diols. A bifunctional MOF catalyst having an appropriate combination of Lewis acid and Lewis basic sites was developed specifically for this process [97]. This material, that is, the IRMOF-3 framework (Zn 4 O(BDC) 3 ) with amino functions in organic linkers was modified by a post-synthesis strategy by alkyl halides resulted in the conversion of -NH 2 to a quaternary ammonium salt species.…”
Section: Post-synthesis Modification Of Organic Linkersmentioning
confidence: 99%
“…Other catalysts such as gold, 21 palladium, 22,23 copper, [24][25][26] rhodium, 27 tungsten, 28,29 zinc, 10,30 lanthanum, [31][32][33] calcium, 34,35 magnesium, [36][37][38][39][40][41] zeolites, 42,43 Naon, 44 alumina, [45][46][47] have been used to produce glycerol carbonate by carbonylation of glycerol with alkyl carbonates, 19,48,49 CO 2 (ref. 30) or urea, [50][51][52][53][54][55] arriving on the desired product with poor (when CO 2 is used) to good yields and selectivity (when alkyl carbonates are used). A more convergent approach tends to arrive on the desired glycerol carbonate during the biodiesel process and good results were obtained up to now (Fig.…”
Section: Introductionmentioning
confidence: 99%